An Investigation into 2D and 3D Shapes Perception - Vanja Čok*; Daria Vlah; Roman Žavbi (Tehnički Vjesnik, 2020)
Numerous research results support the finding that a product's visual appearance is important. In particular, end products or services that have a direct product-user interaction have to be developed in accordance with the taste of the user and the market. The user-centered product should be designed and created according to both the technical requirements and the customer needs, but it should also differentiate itself from the competition. The shape of a product, whether we observe it in 2D or 3D, should communicate various intangible meanings. Our aim was to investigate whether the meaning of bipolar adjectives varies when observing samples of 2D and 3D shapes. The study was conducted using 2D shape contour samples and interactive 3D extruded models that could be rotated in virtual space. In order to determine the relationship between the shape and the user's perception of it, Kansei engineering methodology was used. We collected data with Semantic differential survey using five level Likert scale. The results revealed minor deviations in the users’ perceptions of the 2D and 3D sample shapes.